ANALISIS KESESUAIAN PREDIKSI KEBANGKRUTAN MODEL ALTMAN Z-SCORE, FULMER DAN SPRINGATE TERHADAP OPINI AUDITOR PADA PERUSAHAAN DELISTINGTAHUN 2015 - Rahmadini, Anissa Agustina (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract-This research aims at bankruptcy prediction in PT. Bank Ekonomi Raharja which delisted from The Indonesia Stock Exchange and determine the level of suitability of these predictions with the auditor's opinion on the financial statements. This research is a descriptive study with a sample of companies that delisting from the stock exchange in 2015. Based on processing and analysis of financial data year 2011-2015 results obtained from three models of bankruptcy prediction Springate and Fulmer predicted PT. Bank Ekonomi Raharja went bankrupt during that period, while the method of Altman predicts PT. Bank Ekonomi Raharja are in the category of